2017
DOI: 10.7717/peerj.3184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment of the fecal microbiota in healthy cats and dogs before and during supplementation with fructo-oligosaccharides (FOS) and inulin using high-throughput 454-pyrosequencing

Abstract: Prebiotics are selectively fermentable dietary compounds that result in changes in the composition and/or activity of the intestinal microbiota, thus conferring benefits upon host health. In veterinary medicine, commercially available products containing prebiotics have not been well studied with regard to the changes they trigger on the composition of the gut microbiota. This study evaluated the effect of a commercially available nutraceutical containing fructo-oligosaccharides (FOS) and inulin on the fecal m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 67 publications
4
31
0
1
Order By: Relevance
“…Comparative analyses demonstrated that the bacterial compositions of canine and feline guts differ significantly. We found significantly higher alpha diversity in cats relative to dogs, which also corroborates earlier findings [47,53]. Therefore, together these findings reveal that the DTC approach implemented herein produces results comparable to those obtained using standard techniques in the laboratory.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Comparative analyses demonstrated that the bacterial compositions of canine and feline guts differ significantly. We found significantly higher alpha diversity in cats relative to dogs, which also corroborates earlier findings [47,53]. Therefore, together these findings reveal that the DTC approach implemented herein produces results comparable to those obtained using standard techniques in the laboratory.…”
Section: Discussionsupporting
confidence: 90%
“…Both measures of gut bacterial diversity were higher in cats regardless of rarefaction depth (P<0.01, Kruskal-Wallis test, Fig 1A and S3A Fig), indicating that the feline gut harbors significantly higher bacterial diversity relative to the canine. This observation is consistent with previous reports [47,53].…”
Section: Diversity Differences Between Pet Types Are More Pronounced supporting
confidence: 94%
“…These differences could be due to the specific microbial populations and/or activities in the two animal species. Our observation is in accordance with that reported by Garcia-Mazcorro et al (2015), which evaluating in vivo the effect of different prebiotic supplementation in dog and cat microbiota, concluded that the two species respond differently to the same treatment.…”
Section: Discussionsupporting
confidence: 94%
“…However, these results must be considered with caution since the taxa significantly different for the D1 did not correspond to those found for the D3 group or, in any case, no dose response effect was observed. Moreover, in Figure 3, the individual relative abundances of 2 significant taxa at T0, T14, and T28 indicated a high variability, which can be attributed to age, sex, breed, and other factors related to the environment, as already highlighted by previous research [45,46]. Nonetheless, the influence exerted by the genetics of the host, reported in humans [47] and livestock [48], should also considered among the factors affecting the gut microbiota.…”
Section: Discussionmentioning
confidence: 65%